PRARANCANGAN PABRIK VINYL CHLORIDE MONOMER DARI ETHYLENE DICHLORIDE DENGAN KAPASITAS 100.000 TON/ TAHUN - , RIZAL AGUNG PRAKOSA; , Ir. Wahyu Hasokowati, M.A.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Vinyl chloride monomer is a monomer with chemical formula as C2H3Cl that used widely as poly vinyl chloride (PVC) raw material. Development opportunities of vinyl chloride monomer industry in Indonesia is quite large, considering that Indonesia still buy vinyl chloride monomer from others country to fullfill national needs. The plant is designed to run for 330 days / year with a vinyl chloride monomer production capacity of 100,000 tons / year. The main raw material, ethylene dichloride, required is as much as 188,147.94 ton / year. The method used is the cracking of ethylene dichloride. There are three steps for manufacturing vinyl chloride monomer. Firstly, ethylene dichloride has to be vaporized in order to react in gas phase, this reaction take place in furnace. Secondly, product that come from furnace chilled quickly in quenching tower to avoid side reaction. Finally, purification of vinyl chloride monomer done by distillation process and purification of hidrochloric acid done by absorption process. As a support, utility plant unit supplies as much as 422,407.2069 tons / year of cooling water, 1,234.22 kVA of electricity, up to 3,168,000 m 3 /year of compressed air, and 404,735.6056 tons / year of steam. The plant will be established in the city of Cilegon, Banten province, with consideration of raw material oriented. Cilegon region close to the ethylene dichloride industry, and close to the harbor making it easier to procure raw materials hydroquinone which is imported from China. Plant location close to the sea, so that the source of water for utility plant unit derived from seawater. Calculation of economic evaluation results is fixed capital required equal to $39,539,074.16 and Rp Rp 114.256.735.149,37 and working capital equal to $41,209,452.94 and Rp 9.843.892.711,65. At 100% production rate, obtained ROI before tax of 27,23%, ROI after tax of 13,62%. POT before tax of 2,69 years, POT after tax of 4,23 years, with BEP at 50,14%, SDP at 28,18 %, and 27,2% for DCFRR. Based on consideration of the economic evaluation results, this vinyl chloride monomer plant with capacity 100,000 tons / year worth to be studied further.